Improving the Competence of Pasraman Widya Dharma Management Through Website Training - I Dewa Alit Dwija Putra; I Gusti Agung Rangga Lawe; Ganjar Gumilar (Journal of Innovation and Community Engagement, 2021)
Professional competency improvement for management at Pasraman Widya Dharma in Bandung is very important in this era of globalization. There is a need for partnership with a higher education institution to run an empowerment program in a form of training in using internet website. Website is an easily accessible information media which is suitable to publish information in informal education institutions such as Pasraman. The empowerment is intended to improve the professional competence of staffs and administrators who provide services at institutional facilities within the Bandung Hindu community. The empowerment was implemented using Service Learning method in order to optimize the potential of the community partnership with a focus on training and assistance related to improving the professional competency of the administrators and managers of the Widya Dharma Pasraman Bandung. The professional competency of the managers was observed to be improved significantly based on the result of the training program. This leads to a conclusion that the program is potential to be carried out in continual basis.